THE PROCESS OF STRENGTHENING THE POTENTIAL OF A POST-INDUSTRIAL SOCIETY INDIVIDUAL - ABOUT THE ROLE AND IMPORTANCE OF THE CAREER COUNSELLING PROCESS - Kukla, Daniel Mariusz; Nowacka, Marta Elżbieta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The study is an analysis of the literature on the subject in the area of society's expectations towards the process of career counselling. At present, it seems very important to make adequate educational and vocational choices in the era when knowledge and information becomes more and more important and quickly becomes outdated. It is important to prepare a unit in the counselling process to deal with a permanently and dynamically changing world.The effect of the analyses is to indicate the challenges and needs of the professional counselling process towards the modern society in the current socio-economic realities.